An investigation of factors that determine motorcyclists' adoption of an idle-stop system in Taiwan. Issue 3 (15th March 2016) - Pai, Chih-Wei; Jou, Rong-Chang; Kuo, Ming-Shin
ABSTRACT: To combat gas emissions produced by idling motorcycles at red lights, the Taiwanese government passed an "idle-stop (IS)" bill that requires manufacturers beginning in 2015 to equip 10% of newly manufactured motorcycles with a microchip enabling the idling engines to automatically shut off. Along with safety concerns over the new but controversial technology, the additional charge would influence riders' decisions to adopt the system. This article specifically studies this matter by using a survey that investigated the contributory factors to motorcyclists' adoption of the system. Probabilistic models were estimated using data gathered from 3, 673 motorcyclists in Taoyuan City, Taiwan. Three separate models (by no incentive, purchase support, and annual tax rebate) with mixed logit formulation were estimated to investigate the effects of the variables on respondents' three levels of IS adoption (low, medium, high) and capture potential heterogeneity. Several variables (e.g., female riders) appear to have heterogeneous effects, lending support to the use of mixed logit models in idle-stop research. An annual tax rebate appears to be the most tempting incentive, although it has limited effect on heavy motorcycle users, OAPs (old age pensioners), and those having safety concerns—suggesting that promotional activities (e.g., demonstrations, field operational tests) to enhance market penetration of the technology may be directed toward these groups. Other variables found to be significant determinants of IS adoption include, for example, gender, motorcycle engine size, red-light duration, and when the gasoline price was rising. The policy implications of the results are finally discussed.